PERANCANGAN SISTEM INFORMASI HUMAN RESOURCE DEVELOPMENT BERBASIS WEB MENGGUNAKAN FRAMEWORK ODOO DI PT. NURO INTELIA PROSPERA JAKARTA - Cahyadi Agustin; Firman Rizaldi Yusup (POLITEKNIK PIKSI GANESHA, 2020)
This research aims to analyze, design and build the implementation of Human Resource Development information system at PT NURO INTELIA PROSPERA JAKARTA. research method used is qualitative descriptive method. Data collection techniques used are literature studies, field studies. The method used in system development is waterfall. From the research conducted, it was found that there are problems in the management of Human Resource Development. The integration data management process is still not globally so it is still not effective in data input procedures, data storage, data search and report creation. Therefore, a Human Resource Development information system is created by using Python and PostgreSQL programming languages as a Database. The suggestions given to deal with existing problems include: 1) Optimizing the Human Resource Development system using a system that has been designed, 2) Developing and updating the system to improve the quality of the system so that it can be used further.